Die Schlagbäume heben. Die Kooperation von Archivaren, Historikern und Geschichtsfreunden diesseits und jenseits der deutsch-niederländischen Grenze - Löhr, Wolfgang (Archivfachliche Beiträge, 2020)
Keywords: Archivkunde; Geschichtsschreibung; Grenzgebiet; Grenzüberschreitende Kooperation; Heimatkunde; Niederrhein-Gebiet

The Maas-Rhine Euroregion. A Laboratory for European Integration? - Knippenberg, Hans (Geopolitics, 2004)
„The transborder and trilingual Maas–Rhine Euroregion is often presented as a laboratory for European integration. The authorities in the region promote the image of a region that has ‘always’ been a unity, but which is divided by artificial boundaries – ‘scars of history’ – as a result of power politics. In this essay this image is confronted with the reality of the cross-border interactions and identities of the people involved. This confrontation leads to the conclusion that although there is political, economic and cultural cooperation in the region, the region is not at all politically, economically and culturally integrated. The national border as a physical barrier may have been removed, but the economic, social, juridical and cultural barriers are still there. The unification and integration of the citizens living in the region is being impeded by conflicting national systems of law and regulations, by communication and information media focused on national issues, by nationally oriented infrastructure, and especially by strongly different national cultures and identities. The consequences for European integration in general are analysed by comparing this regional integration with the national integration and nation-building policies of the past.“
Keywords: Euregio Maas-Rhein; Europäische Integration; Grenzüberschreitende Kooperation

Grenzüberschreitende Ordnungspartnerschaft - Mokros, Reinhard (Die Polizei, 2002)
Keywords: Grenzgebiet; Grenzüberschreitende Kooperation; Herzogenrath; Kerkrade; Nordrhein-Westfalen; Polizei

Vom Streitfall zum „Mustergarten Europas“ - Drei Beispiele aus dem Grenzgebiet - Protte, Katja (Deutschland - Niederlande. Heiter bis wolkig. [Begleitbuch zur Ausstellung im Haus der Geschichte der Bundesrepublik Deutschland, Bonn, 22. November 2000 bis 16. April 2001 und im Rijksmuseum, Amsterdam, 26. Mai bis 16. September 2001], 2000)
Keywords: EUREGIO (Körperschaft); Elten; Grenzüberschreitende Kooperation; Herzogenrath; Kerkrade

City-networking and bottom-up development by transborder co-operation. The influence of local authorities in the Saar-Lor-Lux Region - Schulz, Christian (Nationalising and Denationalising European Border Regions, 1800–2000. Views from Geography and History, 1999)
Keywords: Grenzüberschreitende Kooperation; Saar-Lor-Lux

Wisselende perspectieven van grensligging in de geschiedenis van de euregio Maas-Rijn - Jansen, Johannes C. G. M. (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 1997)
Keywords: Euregio Maas-Rhein; Grenzüberschreitende Kooperation

Bestuurlijke vernieuwing in grensgebieden. Intergemeentelijke grensoverschrijdende samenwerking in het Nederlands-Belgisch grensgebied - Kessen, Antoine Alcide Louis Guillaume Marie (1992)
Keywords: Grenzüberschreitende Kooperation

Historische Grenzlandbeziehungen am Niederrhein - Jappe Alberts, Wybe (Landschaft und Geschichte. Festschrift für Franz Petri zu seinem 65. Geburtstag am 22. Februar 1968, 1970)
Keywords: Grenzüberschreitende Kooperation; Niederrhein-Gebiet